PENDIDIKAN PRA NIKAH UNTUK MEWUJUDKAN RUMAH TANGGA SAKINAH, MAWADDAH, DAN RAHMAH PERSPEKTIF AL-QUR’AN DAN AL-HADITS - Saepudin, Saepudin; Miftahudin, Miftahudin; Hanafi, Hanafi (STAI Darul Qalam Tangerang, 2022)
This study aims to describe pre-marital education to realize the household of sakinah, mawaddah, and rahmah perspectives of the Qur'an and Al-Hadith. This research uses qualitative methods of literature studies. The focus of this research is the conditions that must be carried out to achieve the family of sakinah, mawaddah, and rahmah in the Qur'an and Al-Hadith. The instrument of this research is the researcher himself. This research analysis technique uses content analysis techniques. The results of this study are the author can conclude that as a muslim human being, it is recommended to marry and be married. And the intention in the household is only to seek the pleasure of Allah SWT so that his home life becomes a happy family, congratulations, and blessings born and inner, both in the world and in the afterlife, which is by the guidance of Islamic teachings according to the Qur'an and Al-Hadith that has been exemplified by the Prophet Muhammad SAW, as a disciple of tauladan ummah. We can take lessons from how he exemplifies and must be applied in everyday life. In addition to the verses of the Qur'an and the Hadith Texts above, there may still be many other verses and hadiths that can be used as a concept to reach the household that is sakinah, mawaddah and rahmah